A ten-year retrospective study investigating the rate of venous thromboembolism in patients who require immobilization in a total contact lower limb cast. (June 2019) - Tonge, X. N.; Widnall, J. C.; Jackson, G.; Platt, S.
Abstract : Aims: To our knowledge, there is currently no information available about the rate of venous thromboembolism (VTE) or recommendations regarding chemoprophylaxis for patients whose lower limb is immobilized in a plaster cast. We report a retrospective case series assessing the rate of symptomatic VTE in patients treated with a lower limb cast. Given the complex, heterogeneous nature of this group of patients, with many risk factors for VTE, we hypothesized that the rate of VTE would be higher than in the general population. Patients and Methods: Patients treated with a lower limb cast between 2006 and 2018 were identified using plaster room records. Their electronic records and radiological reports were reviewed for details about their cast, past medical history, and any VTE recorded in our hospital within a year of casting. Results: There were 136 episodes of casting in 100 patients. The mean age was 55 years (22 to 91). The mean time in a cast was 45 days (five days to eight months). A total of 76 patients had neuropathy secondary to diabetes. No patient received chemical thromboprophylaxis while in a cast. One VTE (0.7% of casting episodes) was documented. This was confirmed by Doppler scan nine days after removing the cast. Conclusion: The frequency of VTE was higher than that of the general population (0.05%); this is most likely attributable to our patients' apparent increase in VTE risk as suggested by The National Institute for Health and Care Excellence (NICE). These findings suggest that thromboprophylaxis is not routinely indicated in patients who undergo immobilization of the lower limb in a cast, although the risks of VTE should be assessed. While the cast itself does not pose an increased risk, other pathologies, such as active cancer, mean that each individual case needs to be considered on their merit. Cite this article: Bone Joint J 2019;101-B:691–694.